Advances in laser physics and technology - Mohan, Man 1948- (Foundation Books, 2015)
Lasers are created to study the timescale of electron motion in atoms and molecules. They also have wide applications in areas like solid state, plasma physics, nanoscience and defence technology. This book helps readers to master the large variety of physical phenomena and technological aspects involved in laser technology. Besides explaining the physical principles and common techniques of laser science and technology, it also elaborates on topics like High-harmonic Generation (HHG) and strong-field Non-sequential Double Ionization (NSDI), effects of a low energy atto-second pulse, laser spectroscopy, laser cooling and trapping, quantum optics and laser applications. Many important concepts covered include a new test system design of comprehensive characterization of non-imaging laser IR guided missiles, advanced laser and opto-electronics technologies for Low Intensity Conflict (LIC) applications and development of highly advanced laser cavity and resonator for high power chemical oxygen iodine laser at the Laser Science and Technology Centre (LASTEC)